Relative age effect - A study of Norways, Swedens and Portugals U17, U19, U21 and adult team - Hamnvik Sagelv, E.; Nicolaisen Simonsen, J.; Rafoss, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Since Grondin, Deshaies and Nault(1984) discussed a possibility of relative age effect, the phenomenon has been shown in many sports, especially in team sports with physical contact. Relative age effect (RAE) is a phenomenon when an athlete gets benefits of being more physically developed because of when he/she is born in the year, or after the cut-off date. We have been aware of the RAE in over 10 years now, and little is done about it. The consequences is that many talents, who is not that well physically developed yet, is lost due to the small sense of achievement in a young age, this is called drop-out. In adult sports the phenomenon does not occur as much as in youth sports (Musch and Grondin, 2001). Methods: We checked the birth date of all male players who were called up for the U17, U19, U21 and the adult team in Norway, Sweden and Portugal from 2008 until 2012, in football. We divided them into 4 quarters and looked for any significant similarities or differences. We hypothesized that since Portugal is a better football nation than Norway and Sweden, Norway and Sweden should have more players born in the first and second quarter than Portugal. At the same time we checked the 1994- and 1998-world cup team for Norway, because Haulan and Saether(2011) meant that RAE did not occurred in the time when the Norwegian national team qualified for the world cup in 1994 and 1998. Results: The results showed no significant differences in the three nations. It also showed that RAE did not occur as much in adult sports as in youth sports. From 2008 until 2012 it seems that there are more players born in the first and second quarter in 2012 than 2008 for U17 and U19. It also showed that RAE did occur in the two Norwegian world cup teams (1994 and 1998). Discussion: These results show that these three nations have not taken RAE under consideration when they call up youth players for the national team. Also, by comparing our results with Helsen et. al.(2012), Peterson(2004) and Ripegutu and Eide(2008), these nations have not taken any consideration for RAE from 2000 until 2012. We proposed three solutions to RAE. One is that you must have 25 % of the players you call up to the national team in each quarter. Another one is weight and height national teams instead of U16, U17 and so on. The last solution is rotating cut-off date. For each year the cut-off date is moved, in that way every month gets to be the first month after the cut-off date. This last solution is Helsen et. al.(2012) idea.